Evaluation of Phytochemicals, Mineral Constituents and Antimicrobial Activity of Leaf, Bark and Flower Extracts of Firmiana Colorata - Bi Bi Hajira; Geraldine Menezes (International Journal of Pharma and Bio Sciences, 2021)
Firmiana colorata is a medium sized deciduous tree known to be used by the tribal people as a remedy to cure general weakness, fever and jaundice. Phytochemicals are the secondary metabolites produced by the plants for its adaptation and demonstrate high medicinal value. The present study deals with the evaluation of preliminary physicochemical and phytochemical properties, mineral analysis, antimicrobial properties and determination of MIC in the study samples of Firmiana colorata. The preparation of leaves, bark and flower extracts were carried out by successive solvent extraction methods using Soxhlet apparatus. The physicochemical and phytochemical analysis was carried out using standard laboratory qualitative test methods. The mineral analysis was performed by X-ray fluorescence spectroscopy. The antimicrobial activity was determined by agar well diffusion method and minimum inhibition concentration by Resazurin based microtiter dilution assay. The physicochemical evaluation revealed sticky consistency in all test extracts and low moisture content in crude samples. The mineral analysis showed the presence of important minerals like iron, zinc, copper and molybdenum. The phytochemical evaluation showed the presence of secondary metabolites-alkaloids, phenols, tannins, saponins, steroids, carbohydrates, flavonoids and terpenoids. The antimicrobial activity was high in bark and leaf extracts and low in flower extracts. Firmiana colorata is a plant with medicinally important phytochemicals and has scope for its antimicrobial properties.